Мonitoring the capacitor charge voltage in the pulse voltage generator using the accelerator of relativistic electron beams - Batrakov, A.B.; Glushko, E.G.; Zinchenko, A.A.; Lonin, Yu.F.; Ponomaryov, A.G.; Fedotov, S.I. (Вопросы атомной науки и техники, 2018)
Noise-protected high charge voltage meter was manufactured using terminal capacitors of the four-channel pulse
voltage generator (PVG). The noise protection is provided by the use of communication lines with fiberoptic cables.
This measuring device is successfully used for the relativistic electron beam (REB) accelerator «Temp-B» and it
provides the measurement accuracy of ~ 0.5% in the electromagnetic noise environment. Виготовлено перешкодозахищений вимірювач високої зарядної напруги на кінцевих конденсаторах чотириканального генератора імпульсної напруги (ГІН). Перешкодозахищеність забезпечується застосуванням
ліній зв'язку з використанням оптоволоконного кабелю. Даний вимірювач успішно використовується на
прискорювачі РЕП «Темп-Б» і забезпечує точність вимірювання ~ 0,5% в умовах сильних електромагнітних
перешкод. Изготовлен помехозащищенный измеритель высокого зарядного напряжения на оконечных конденсаторах четырехканального генератора импульсного напряжения (ГИН). Помехозащищённость обеспечивается
применением линий связи с использованием оптоволоконного кабеля. Данный измеритель успешно применяется на ускорителе РЭП «Темп-Б» и обеспечивает точность измерения ~ 0,5% в условиях сильных электромагнитных помех.